Influence of haemosporidian infection status on structural and carotenoid‐based colouration in the blue tit Cyanistes caeruleus. (31st October 2018) - Janas, Katarzyna; Podmokła, Edyta; Lutyk, Dorota; Dubiec, Anna; Gustafsson, Lars; Cichoń, Mariusz; Drobniak, Szymon
Abstract : Hypotheses postulating parasite‐mediated mate choice intrinsically assume that parasitic infections deteriorate the quality of male ornamentation. Although this assumption has often been studied in the context of carotenoid‐based colouration, only few studies investigated this with reference to structural feather colouration, which in many species plays a vital role in sexual selection. Here, using a three‐years dataset from a wild blue tit Cyanistes caeruleus population, we examined the relationship between the haemosporidian infection status and the structural as well as the carotenoid‐based colouration of adult birds. Furthermore, we investigated potential differences in the impact on feather colouration between two examined parasite genera: Plasmodium and Haemoproteus . For analysis of the feathers spectral reflectance we used both the tristimulus model and the avian tetrahedral colour space model, incorporating visual phenotype of the blue tit. Contrary to expectations we found that infected birds showed higher brightness, in both the structural and the carotenoid‐based colours. We also found no differences in the feather colouration between birds infected with Plasmodium and Haemoproteus . Observed pattern might be best explained by the parasite‐mediated selection hypothesis, as only individuals of superior quality should be able to survive the acute stage of infection and therefore they could produce more elaborate ornamental colouration.